RELASI HUKUM ISLAM DAN KEKUASAAN SERTA PERBEDAANNYA DENGAN HUKUM BARAT - Shinwanudin, M.; Zuhriyyah, Lailatuz (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2022)
Discussing the current relation of Islamic law and power, the position of Islamic law in the legal system in Indonesia is increasingly gaining juridical recognition with the enactment of Islamic law in the form of rules and regulations which have implications for the existence of social, cultural, political and legal institutions. The difference between Islamic law and Western law comes from the source of each law. Islamic law is taken from the texts of the Qur'an and Sunnah, ijma' and qiyas. While the Western legal system is a modern legal concept adopted by the majority of nations in the world.